The Influence Of Procedural Discrepancies, Supervisory Weaknesses And Administrative Errors On Service Performance At The Telkom Office In Bengkulu City - Astuty, Kamelia; Aulianisa, Nabela; Pratama, Yoga Anugrah; Herlyaminda, Evi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the influence of procedural nonconformity, weak supervision, and administrative errors on service performance at the Telkom Office in Bengkulu City. The background of this research is based on the persistent issues in public service delivery, such as procedures not being followed according to operational standards, weak supervisory functions, and administrative errors that impact customer satisfaction. The research method employed is a quantitative approach, with data collected through questionnaires distributed to 263 respondents. The research instruments were tested for validity and reliability using SPSS. The results indicate that procedural nonconformity, weak supervision, and administrative errors have both partial and simultaneous significant effects on service performance at the Telkom Office in Bengkulu City. These findings provide important implications for management to improve work procedures, strengthen the supervision system, and enhance administrative quality to improve overall service performance.